2021
DOI: 10.3389/fphys.2021.652029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Short-Term Resistance-Training Program on Heart Rate Variability in Children With Cystic Fibrosis—A Randomized Controlled Trial

Abstract: Background: Cystic fibrosis (CF) affects the autonomic nervous system (ANS) and exercise in healthy children modulates the interaction between sympathetic and parasympathetic activity. This study aimed to evaluate the effects of a short-term resistance exercise program on heart rate variability (HRV) in children and adolescents with CF.Methods: A randomized controlled trial was carried out in children diagnosed with CF aged 6–18 years. Individuals were divided into two groups: control (CON) and resistance-trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 40 publications
(63 reference statements)
0
18
0
1
Order By: Relevance
“…Additionally, chronotropic incompetence is crucial in limiting exercise in patients with CF [24]. Finally, it was described that cardiac ANS could be altered in CF, causing heart rate variability (HRV) abnormalities [25]. The echocardiographic findings of our patients showed no underlying LV systolic and diastolic and RV systolic function abnormalities, except for marginal results of RV systolic function.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Additionally, chronotropic incompetence is crucial in limiting exercise in patients with CF [24]. Finally, it was described that cardiac ANS could be altered in CF, causing heart rate variability (HRV) abnormalities [25]. The echocardiographic findings of our patients showed no underlying LV systolic and diastolic and RV systolic function abnormalities, except for marginal results of RV systolic function.…”
Section: Discussionmentioning
confidence: 61%
“…However, it remains unknown if the exact beneficial mechanisms of exercise also apply to LV dysfunction in CF patients. Interestingly, the study of Estévez-González et al has shown that an 8-week resistance-training program improved the sympathovagal balance, leading to an increase in HRV [25].…”
Section: Discussionmentioning
confidence: 99%
“…Data from multiple studies (males, N sizes ranging from 2104 to 803,505) indicate that a one SD higher systolic BP in adolescence increases risk for ischemic stroke (Hazard Ratio [HR], 1.04; 95% CI 1.02–1.07) and hemorrhagic stroke (HR, 1.12; 95% CI 1.07–1.17) in adulthood [ 38 ], that both elevated systolic and diastolic BPs in adolescence increase risk for cardiovascular mortality in adulthood [ 39 ], and that elevated resting HR in adolescence is associated with heart failure, dilated cardiomyopathy [ 40 ], and cardiovascular and all-cause mortality [ 41 ]. Fortunately, interventions to address strength deficits improve markers of vascular flow in lean children [ 42 ], measures of glycemic control in children with insulin resistance [ 43 ], function in children with cerebral palsy, [ 44 ] frequency domain components of HR variability in children with cystic fibrosis [ 45 ], and both skeletal muscle mass and visceral adiposity in children and adolescents with obesity [ 46 ]. Interventions to promote weight loss such as diet, medications, and resistance and aerobic training, are also beneficial in pediatric populations [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence has shown that a short-term exercise resistance training program was effective in modulating HRV in children and adolescents with CF. 37 …”
Section: Discussionmentioning
confidence: 99%
“…In children and adolescents with CF presenting mild-to-moderate lung function impairment and a good physical state, 57.9% of individuals presented at least one altered HRV variable. 37 Based on the study by Gasior et al. , 21 which defines the normalization of HRV indices for school-aged children, we have used the SDNN vagal modulation index of the sample at rest to show that individuals with altered SDNN had worse lung function (FEV 1 and FVC) and less exercise capacity (distance covered in absolute and percentual values).…”
Section: Discussionmentioning
confidence: 99%